Analysis of Development of Archiving Regulation from Time to Time in Indonesia - Rodin, Rhoni (D3 Teknisi Perpustakaan Fakultas Vokasi Universitas Airlangga, 2019)
Background of the study: This research belongs to the literature study since it is carried out by exploring information and documentation relating to archiving regulationsPurpose: This study aims to analyze the development of archiving regulations in Indonesia from time to time.Method: Analyzing data using descriptive analysis methods.Findings: The results showed that the development of archiving regulations in Indonesia showed a positive trend, as this was shown by the issuance of several regulations relating to archival issues from the Dutch colonial era and the independence of Indonesia in 1945 up until the issuance of Law No. 43 of 2009 during the reform era recently.Conclusion: All archiving laws or regulations are basically for the existence of archives and archives very important for society, government and the Indonesian Nation.